Comparison of nursing doctoral programs in Iran and the University of Massachusetts Boston: A comparative study - Malihe Ameri; Monir Nobahar; Hasan Babamohammadi (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: Learning about the world's successful educational systems in the field of nursing education can be helpful in planning, especially in the doctoral program, and lead to an increase in the quality of education in this field. Therefore, the present study was conducted with the aim of a descriptive and comparative comparison of the curriculum of nursing doctoral programs in Iran and the University of Massachusetts Boston. Materials & Methods: The present study is a descriptive-comparative study. To compare the doctoral nursing curricula of Iran and Boston Massachusetts, related articles and resources along with library studies based on Bereday's four-stage model, including description, interpretation, proximity, and comparison were analyzed. Results: Integration of the curriculum with a focus on nurse participation in health policies, educational content related to defined roles and more emphasis on educational courses, admission of undergraduate doctoral students, the existence of part-time and full-time courses, and having the practice-focused program alongside Ph.D. were important features of Boston University curriculum. The nursing doctoral curriculum in Iran is done only full time and from master's degree and in a centralized manner. The educational courses do not meet the needs of society and the only nursing doctoral program in Iran is Ph.D. Conclusion: Boston's nursing Ph.D. curriculum has been developed with a comprehensive view of the real perceived needs of the nursing profession and society. The results of the comparison can be useful in revising Iran's nursing Ph.D. curriculum to improve educational quality.